Pengaruh Artis Endorser Terhadap Minat Mahasiswa Membeli Shampoo Pantene - Chandra Satya Bintara; Faiq Rivaldy; Sisilia Yuanita Sutarso; Muhamad Nastain; Nafida Hetty Marhaeni (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2022)
Person’s buying interest are usually influenced by many factors, and one ofiot is the celebrities as endorsers that used as a promotional media in the form of advertising. By using celebrities as endorsers, someone will have interest in buying particular product. Therefore, the purpose of this study was to find out whether the celebrities’ endorsers have an influence on increasing interest in buying Pantene shampoo. The population in this study were 266 students of the Communication Science Study Program, Universitas Mercu Buana Yogyakarta class of 2021, while the sample for this study is using the Krejie and Morgan sampling technique with 155 students. The instrument that is used in this research is the celebrities’ endorsers and buying interest questionnaire which has been modified by the researcher. This type of research is quantitative research with a mixed methods approach. The obtained data were then analyzed using SPSS software. The results of the study showed celebrities as endorsers have an influence on the intention to buy Pantene shampoo. The magnitude of the effect is 15,4%, so that the other factors as much as 84,4% are influenced by other variables that isn’t examined. Furthermore, there were no differences between male and female regarding the influence of celebrities as endorsers on purchase intention of Pantene shampoo.